Performance analysis of optimized heartbeat-based reliable NEMO Home Agent - Abdelgadir, Abdelgadir Tageldin (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2011)
Network mobility as a service is provided by the network mobility (NEMO) protocol in IPv6 environments. NEMO is an extension to Mobile IPv6 (MIPv6), and thus inherits the same reliability problems of (MIPv6). MIPv6 is not reliable because the Home Agent (HA) is a single point of failure. In order to provide real-time services such as voice over IP (VoIP) and web conferencing for MIPv6 networks, not just reliability but also high availability should be considered as part of any solution intended to be deployed in Mobile IPv6 networks. Many approaches have been taken to solve the problem of HA as a single point of failure. In this thesis, a study using an experimental approach done on a highly available home agent solution is presented. The solution is compared to a home agent reliability protocol implementation. In the implemented solution, failure detection and recovery is handled by HA. Recovery time achieved was below 100ms. Therefore, recovery is transparent to the mobile network. In the solution, HA redundancy was used to provide the high availability feature and achieve recovery times suitable for real-time applications. The main contribution of the research is the implementation of a highly available home agent in a real test bed and presenting the results from the performance analysis of the implemented solution.